Effects of bariatric surgery on markers of subclinical atherosclerosis and endothelial function: a meta-analysis of literature studies - Lupoli, R; Di Minno, M N D; Guidone, C; Cefalo, C; Capaldo, B; Riccardi, G; Mingrone, G (International Journal of Obesity, 2016)
Background/Objectives: Several studies confirmed a significantly increased carotid intima-media thickness (IMT) and impaired flow-mediated dilation (FMD) and nitrate-mediated dilation (NMD) in obese subjects, but few data are available on the effects of bariatric surgery on these markers of cardiovascular (CV) risk. We performed a meta-analysis of studies evaluating changes in IMT, FMD and NMD in obese patients after bariatric surgery. Methods: A systematic search was performed in the PubMed, Web of Science, Scopus and EMBASE databases without any language or publication year restriction. The last search was performed in January 2015. In addition, the reference lists of all retrieved articles were manually reviewed. Prospective studies evaluating the impact of bariatric surgery on the markers of CV risk were included. Changes in IMT, FMD and NMD after bariatric surgery were expressed as mean differences (MD) with pertinent 95% confidence intervals (95% CIs). IMT has been expressed in millimeters (mm); FMD and NMD as percentage (%). Impact of clinical and demographic features on effect size was assessed by meta-regression. Results: Ten articles (314 obese patients) were included in the analysis. Six studies contained data on IMT (7 data sets; 206 patients), 8 studies on FMD (9 data sets; 269 patients) and 4 on NMD (4 data sets; 149 patients). After bariatric surgery, there was a significant reduction of IMT (MD: −0.17 mm; 95% CI: −0.290, −0.049; P =0.006) and a significant improvement in FMD (MD: 5.65%; 95% CI: 2.87, 8.03; P <0.001), whereas NMD did not change (MD: 2.173%; 95% CI: −0.796, 5.142; P =0.151). Interestingly, percentage of changes in the body mass index were associated with changes in IMT ( Z =11.52, P <0.001), FMD ( Z =−4.26, P <0.001) and NMD ( Z =−3.81, P <0.001). Conclusions: Despite heterogeneity among studies, bariatric surgery is associated with improvement of subclinical atherosclerosis and endothelial function. These effects may significantly contribute to the reduction of the CV risk after bariatric surgery.